(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article delves into the nuanced understanding of instructional methodologies and approaches in language education, highlighting the distinctions between ’method’ and ’approach’ as articulated by scholars. Through the lens of Tavokoli & Jones (2018), the distinction is clarified: ’method’ pertains to specific procedures and techniques employed by teachers, while ’approach’ encompasses broader principles guiding their selection. Emphasizing the pivotal role of effective instructional practices in fostering L2 mastery, the article advocates for a comprehensive approach that prioritizes communication skills. It explores the efficacy of Communicative Language Teaching and Cooperative Language Learning approaches, aligning them with the diverse needs of learners. Furthermore, it delves into the application of Krashen’s Hypotheses, particularly the Natural Order, Input, and Effective Filter hypotheses, in informing instructional strategies. By fostering an environment conducive to meaningful interaction and minimizing emotional barriers, educators can facilitate a dynamic and effective language learning process.